Management of the Science and Tahfidz Excellence Class Programs Based on Academic and Spiritual Outputs at MTs Masalikil Huda Tahunan Jepara - Mafrikha Noor Rizkia; Abdul Wahid (Universitas Negeri Malang, 2026)
Abstract: This study aims to analyze the management of science and tahfidz excellence class programs based on academic and spiritual outputs at MTs Masalikil Huda Tahunan Jepara. The study focuses on the functions of planning, organizing, implementation, and evaluation, as well as the supporting and inhibiting factors affecting the achievement of each program's intended outputs. This research employed a qualitative approach using a case study design. The research participants consisted of the principal, the vice principal for curriculum affairs, teachers of the science excellence program, tahfidz teachers, and students enrolled in the science and tahfidz excellence class programs. Data were collected through interviews, observations, and documentation, and were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the management of the science and tahfidz excellence class programs is implemented through the functions of planning, organizing, implementation, and evaluation, which are designed based on the intended outputs of each program. The science excellence program is managed to achieve academic outputs in the form of academic achievement, critical thinking skills, research competence, and competition readiness, whereas the tahfidz excellence program is managed to achieve spiritual outputs through Qur'an memorization targets and the development of students' religious character. These differences in output serve as the basis for designing the management functions of each program. The success of the programs is supported by teachers' commitment, the utilization of educational technology, and the madrasah's religious culture. Meanwhile, the main challenges include limited educational facilities and infrastructure, low learning motivation among some students, insufficient parental involvement, and limited supervision in the non-boarding tahfidz program. The findings further indicate that program management designed based on academic and spiritual outputs effectively supports the achievement of each program's objectives and contributes to enhancing the competitiveness of the madrasah. Keywords: program management; science excellence class; tahfidz excellence class; academic output; spiritual output